2014
DOI: 10.1038/ngeo2304
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of climate to cumulative carbon emissions due to compensation of ocean heat and carbon uptake

Abstract: Climate model experiments reveal that transient global warming is nearly proportional to cumulative carbon emissions on multi-decadal to centennial timescales 1-5 . However, it is not quantitatively understood how this near linear dependence between warming and cumulative carbon emissions arises in transient climate simulations 6,7 . Here, we present a theoretically-derived equation of the dependence of global warming on cumulative carbon emissions over time. For an atmosphere-ocean system, our analysis identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 25 publications
6
128
0
1
Order By: Relevance
“…Also, the ranges of the Transient Climate Response to Emissions, TCRE, in the observation-consistent and simulation-consistent model ensembles are comparable to previous estimates based on models and Gillet et al 2013;Matthews et al 2009;Zickfield et al 2009Zickfield et al , 2012 and observationally constrained theory (Goodwin et al 2015). These agreements for the ECS, TCRE and projected warming ranges imply that the WASP model presented here ( Fig.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Also, the ranges of the Transient Climate Response to Emissions, TCRE, in the observation-consistent and simulation-consistent model ensembles are comparable to previous estimates based on models and Gillet et al 2013;Matthews et al 2009;Zickfield et al 2009Zickfield et al , 2012 and observationally constrained theory (Goodwin et al 2015). These agreements for the ECS, TCRE and projected warming ranges imply that the WASP model presented here ( Fig.…”
Section: Discussionsupporting
confidence: 71%
“…The WASP (simulation-consistent) ensemble contains 182,500 ensemble members that are consistent with 8 historic constraints based on the simulated historic ranges of the CMIP5 ensemble. The WASP (observation-consistent) ensemble contains 14,500 members that are consistent with 8 historic constraints from observations Goodwin et al (2015), with additional terms for radiative forcing from non-CO 2 agents (Meinshausen et al 2011) and for equivalent carbon emissions from the ocean temperature-CO 2 solubility feedback (Goodwin and Lenton 2009). A full description of the WASP model, including the model equations, is given in the "Appendix" section.…”
Section: Efficient Earth System Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For future climate changes studies, the response of atmospheric CO 2 concentrations (and hence climate) to changes in terrestrial carbon storage can be calculated using the transient response to cumulative emissions (TRCE) approach (Gillett et al, 2013), which demonstrated proportionality between carbon emissions and temperature rise (Goodwin et al, 2015). We include these estimates for completeness.…”
Section: Methodsmentioning
confidence: 99%